(untitled) (River Edge, NJ, 2003)
This book provides an update on our understanding of strong interaction, with theoretical and experimental highlights included. It is divided into five sections. The first section is devoted to the investigations into and the latest results on the mechanism of quark confinement. The second and third sections focus respectively on light and heavy quarks (effective field theories, Schwinger–Dyson approach and lattice QCD results). The fourth section deals with the deconfinement mechanism and quark–gluon plasma formation signals. The last section presents highlights of experiments, new physics beyond QCD, and nonperturbative approaches in other theories (strings and SUSY) that may be useful in QCD.
Keywords: Quark confinement,Hadrons,Quantum chromodynamics; Sự giảm quac,Hạt cơ bản